Another cup of tea? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Government of Uganda has dismantled the Uganda Tea Authority (UTA) and the Uganda Tea Growers Corporation (UTGC) and is establishing a single tea board. The two bodies were not functioning well in reviving the tea sector, once the country s...